Performance evaluation of pilot-scale A2O reactor as a biological nutrient removal from municipal wastewater - Lee, Patricia C. (Animo Repository, 2021)
With the developments in industries and increase in population, water pollution in the Philippines has become serious a concern wherein immediate action should be implemented to prevent detrimental effects. To monitor the water quality, DENR have stipulated new regulations on the effluent quality standards as declared in the DENR Administrative Order (DAO) 2016-08. Currently, wastewater treatment facilities in the Philippines are yet to comply with the new regulations. Several biological nutrient removal technologies have been investigated in many countries to address extreme water pollution. This includes the anaerobic/anoxic/oxic (A2O) and modified Ludzack - Ettinger (MLE) processes. These BNRTs are known to provide high nutrient removal efficiencies, especially for nitrogen and phosphorus treatments. With this, this study conducted an evaluation on the performance of a pilot-scale A2O and MLE reactor. For two operational runs, the removal efficiencies of the system were investigated through the analysis of the influent and effluent water streams. Overall, nutrient removal is evident in the ammonia-nitrogen and phosphorus concentrations as well as TSS and COD. The wastewater was characterized to have a low strength quality which denoted a low carbon food source for microbial biomass. Denitrification was not effective in the system due to the high DO levels noted in the anoxic reactor. The installation of return activated sludge (RAS) at the second run of treatment allowed higher removal efficiencies for ammonia-nitrogen and phosphorus. Subsequently, higher nitrate levels were reported due to the recycled nitrate-rich activated sludge. Several operational issues have disrupted the removal efficiencies and caused undesirable values in the parameters such as excessive DO levels in the anoxic tank and low MLSS concentrations in the oxic chamber. It was recommended to conduct operation modifications in the system. Furthermore, a longer duration of the study was suggested to achieve sufficient acclimatization period and stable performance for optimal results.